Teachers’ professional development in community campuses of TU: Expectation and responsibility - Ghimire, Nani Babu (Siddhajyoti Interdisciplinary Journal, 2020)
Teachers' professional development programme enables teachers to develop the knowledge and skills they need to address the students' learning. It assists the teachers to improve their instruction for the improvement of student learning achievement and better performance of community campuses. The purpose of this study was to explore the significance of Teachers’ Professional Development (TPD) to the teachers of community campus with their expectation, and responsibility. Qualitative case study design was adopted and three teachers were purposively selected from three distinct community campuses of Sindhuli district. Data were collected through semi-structured open-ended interview guidelines. Collected raw data were analysed using thematic analysis. The finding exposed that only teaching in the classroom is not enough for teachers' professional development. Besides, the teachers should participate in training, research work, writing journal article, teachers discussion programmes, learning from media, self/further study, attending in seminars/work-shops/conferences. TPD helps the teacher to develop professional knowledge, skills, new techniques and technology of teaching. The teachers are themselves supposed to be conscious and initiative for their professional developments.